Analysis of the Factors that Affect the Implementation of E-Government in Indonesia - Karunia, R Luki; Budiaji, Rahmad; Suzana, Reni; Dewi, Kurnia Sari; Prasetyo, Johan Hendri (International Journal of Membrane Science and Technology, 2023)
The research had purpose to investigated further related to the factors which affecting the implementation of e-Government (e-Gov) within the Ministry of Communication and Informatics of the Republic of Indonesia. This research was designed by the Quantitative-Descriptive method through a causality approach. The sample for this study amounted to 104 respondents who were randomly selected by a simple random sampling technique. The data analysis method used was PLS-SEM to test the research hypothesis. The results strongly suggested that information technology and human resource had significantly positive impact on the implementation of e-Gov, both partially and simultaneously. The findings of this research also demonstrate that the provision of applications related to the main duties and functions of employees is necessary. In addition, solving problems that occur at work also is the most essential thing that should be done in implementing e-Gov.